Optimalisasi Kesehatan dan Gizi Lansia Melalui Penyuluhan dan Pendampingan Gizi di Kelurahan Cipadu Jaya: Optimizing Health and Nutrition of the Elderly through Nutrition Counseling and Assistance in Cipadu Jaya Village - Ngadiarti, Iskari; Muntikah, Muntikah; Noviani, Ani; Nixon, Aurasyifa Salsabila (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The percentage of the elderly population in RW 01, Cipadu Village, has increased, indicating that in 2023, this area has entered the era of an aging population, where the percentage of the population aged 60 and above is almost reaching 10% or more. The purpose of this community service is to raise awareness among the community about a healthy lifestyle to prevent non-communicable diseases, to practice the preparation of healthy drinks, and early detection of health status through anthropometry and stick test methods. The methods used in this community service include counseling with the theme "Optimizing the Health and Nutrition of the Elderly," practical measurement of nutritional status, screening for Non-Communicable Diseases using the stick test method, followed by guidance and monitoring of older people. There has been a 21.1% increase in knowledge about balanced nutrition for older people and the preparation of healthy drinks. Screening for nutritional status shows that 37.3% are obese. Health checks indicate that out of 51 people, 78.4% have high blood pressure, 66,7% have high cholesterol levels, 43,1% have high uric acid levels, and 5.8% have diabetes. Assistance for one month on adopting a healthy lifestyle, including getting used to new healthy drinks, has reduced weight and blood pressure, but blood sugar and cholesterol have not consistently improved. Practicing a healthy lifestyle with assistance has not optimally achieved a healthy status. Therefore, periodic education on elderly nutrition and early detection is necessary to maintain and monitor healthy lifestyles.